Adaptation to Peripheral Flicker - ANSTIS, STUART (Vision research (Oxford), 1996)
With strict fixation, a flickering disk presented in the peripheral retina rapidly appeared to lose contrast and stop flickering, owing to adaptation. Subjects measured this adaptation by continually adjusting the flicker amplitude of a peripherally viewed disk to hold it just at threshold. (1) The contrast threshold for flicker increased logarithmically over time. (2) The slope of the temporal decay function increased with eccentricity (1-16 deg) and with decreasing disk size (8 deg-3.6 min arc). (3) M-scaling the stimulus size could abolish the dependence upon eccentricity for small disks, but not completely for large disks. (4) The temporal decay rate increased with flicker rate (3-15 Hz), as though each cycle of flicker elevated contrast threshold equally.